Recent insights on the genetics and epigenetics of endometriosis. Issue 2 (30th November 2016) - Borghese, B.; Zondervan, K.T.; Abrao, M.S.; Chapron, C.; Vaiman, D.
Abstract : Endometriosis is a gynecologic disease affecting up to 10% of the women and a major cause of pain and infertility. It is characterized by the implantation of functional endometrial tissue at ectopic positions generally within the peritoneum. This complex disease has an important genetic component with a heritability estimated at around 50%. This review aims at providing recent insights into the genetic bases of endometriosis, and presents a detailed overview of evidence of epigenetic alterations specific to this disease. In the future, these alterations may constitute therapeutic targets for pharmacological compounds able to modify the epigenetic code. Abstract :